EFFECT OF CONCENTRATION ON KINETICS AND THERMODYNAMICS PARAMETER IN THE Cu (II) REMOVAL BY ACTIVATED ZEOLITE - Moh. Azhar Afandy; Fikrah Dian Indrawati Sawali (JURNAL INTEGRASI PROSES, 2024)
Adsorption is a commonly used technique for removing heavy metals, particularly Cu (II), due to its efficiency, cost-effectiveness, simple operation, high stability, and excellent selectivity. This study aims to investigate the impact of varying Cu (II) concentrations on the kinetic and thermodynamic parameters during the adsorption process. The adsorption of Cu (II) by activated zeolite was conducted in several batches, using various initial concentrations (20-120 mg/L) and for varied operating time (30-180 minutes). Various kinetic models have been used to evaluate kinetic rate parameters and maximum adsorption capacity, calculated using linear regression equations. Thermodynamic studies were conducted at different temperatures (303-318 K). The study's results indicate that the concentration has a comparable impact on Cu (II) adsorption by activated zeolite, suggesting a pseudo-second-order equation. As the concentration of Cu (II) increases, so do the adsorption capacity (qe) and adsorption rate. At a Cu (II) concentration of 120 mg/L, the adsorption capacity and rate were the maximum, with qe= 5.6054 mg/g, k2 = 64.2279 g.mg-1.min-1, and Coefficient Correlation value (R2) = 0.9998. The ΔG° value suggests that the adsorption process happens spontaneously and through physical adsorption. On the other hand, the ΔH° value reveals that it happens endothermic.